2021
DOI: 10.5194/tc-2021-195
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of Northern Hemisphere snow water equivalent in CMIP6 models with satellite-based SnowCCI data during 1982–2014

Abstract: Abstract. Seasonal snow cover of the Northern Hemisphere (NH) is a major factor in the global climate system, which makes snow cover an important variable in climate models. Monitoring snow water equivalent (SWE) at continental scale is only possible from satellites, yet substantial uncertainties have been reported in NH SWE estimates. A recent bias-correction method significantly reduces the uncertainty of NH SWE estimation, which enables a more reliable analysis of the climate models' ability to describe the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 0 publications
6
8
0
Order By: Relevance
“…For most of the grids, model M1 presented clearly higher R ‐squared values than model M2, though both models showed low R ‐squared values in the southeastern part of China possibly related with the low SD there (Figure 4a). Precipitation was found to be more important than air temperature for CMIP6's winter SD simulation, according to the comparison of the results from error models M3 (only considering precipitation errors) and M4 (only considering temperature errors), which is consistent with previous studies (Kouki et al., 2021). However, this study further revealed the importance of simultaneously considering both errors of precipitation and of temperature.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…For most of the grids, model M1 presented clearly higher R ‐squared values than model M2, though both models showed low R ‐squared values in the southeastern part of China possibly related with the low SD there (Figure 4a). Precipitation was found to be more important than air temperature for CMIP6's winter SD simulation, according to the comparison of the results from error models M3 (only considering precipitation errors) and M4 (only considering temperature errors), which is consistent with previous studies (Kouki et al., 2021). However, this study further revealed the importance of simultaneously considering both errors of precipitation and of temperature.…”
Section: Resultssupporting
confidence: 90%
“…The error model M1 explained on average 67.7% of the variance of SD errors (Figure 4b), indicating that precipitation and air temperature were major error sources in the winter SD simulated by CMIP6 models. Previous studies have also noted the effects of precipitation and air temperature on the snow simulation by CMIP6 models (Kouki et al., 2021; Zhong et al., 2021), but they have not previously been identified as major factors. Here, new insights into the error attribution of CMIP6 snow simulations reveal that the accumulated errors in precipitation and temperature in prior months play a key role, in addition to those errors in the current month under consideration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…475 Changes in snow have implications for the society of Arctic communities where snow may impact many resources (Huntington et al, 2004), and for global climate change (Overland et al, 2019) and carbon cycles (Rogers et al, 2011;Arndt et al, 2020). Thus, understanding how to better model snow distribution and the important features involved in snow distribution is fundamental to improving how we interpret, and plan for, changing Arctic snow in the future (Zhu et al, 2021;Kouki et al, 2021;Mudryk et al, 2020). 480…”
Section: Discussionmentioning
confidence: 99%